Prevalence, Associated factors of Viral Load Suppression and Effect of Intensified Adherence Counselling among Adolescents on ART at Kisenyi, Kawala and Kitebi Health Centres. A Retrospective Chart Review. - Kansiime, David; Gwokyalya, Violet (Student's Journal of Health Research Africa, 2022)
Background: Viral Load Suppression (VLS) is a product of awareness of a positive HIV diagnosis and adherence to ART. Adolescents on ART should virally suppress within six months of ART to live longer, boost their immune system and reduce chances of transmitting the HIV yet literature shows that adolescents are not virally suppressing as adults. The purpose of this study is to therefore assess the prevalence, associated factors of viral load suppression, and effect of intensified adherence counselling among adolescents on ART at Kisenyi, Kawala, and Kitebi Health Centers Methodology: The study utilized a retrospective chart review design. The study population included individual records of adolescents who had been on ART for at least six months from 1st January 2017 to 31st December 2020. Data were analyzed using both univariate and bivariate analysis to be able to describe the data and establish the associations between independent and dependent Variables. Results: The mean age of the 196 study respondents was 15 (SD 3.4). More than half (53%, N=103) of the respondents were aged 15-19 years while 47% (N=93) were aged between 10-14 years. The prevalence of viral load non-suppression after six months of ART was 36% (n-70), and sixty-nine percent (n-48) of the unsuppressed adolescents were females compared to males (31, n=22). Sixty-nine percent (47) of the unsuppressed adolescents were in primary school while 33% (n=23) of the Anglicans were virally unsuppressed. Recommendations: Health facilities should offer resistance testing to all unsuppressed adolescents before enrolment into the IAC program, IAC should be considered primarily for those adolescents identified to have adherence challenges without resistant mutant strains. Conclusion: it is also evident that not all adolescents who enroll in IAC program benefit from it as shown by the 38% of the adolescents who did not suppress following IAC.